Corrigendum: Modelling consumer satisfaction based on online reviews using the improved Kano model from the perspective of risk attitude and aspiration - Zhao, Meng; Zhang, Chenxi; Hu, Yiqi; Xu, Zeshui; Liu, Hao (Technological and Economic Development of Economy, 2021)
Meng Zhao, Chenxi Zhang, Yiqi Hu, Zeshui Xu, Hao Liu, authors of the article “Modelling consumer satisfaction based on online reviews using the improved Kano model from the perspective of risk attitude and aspiration”, published in Technological and Economic Development of Economy, 27(3), 550–582, https://doi.org/10.3846/tede.2021.14223 inform that names of the second, third and fourth authors appeared with hyphens and would like to make the following correction in the authorship as follows:Meng ZHAO, Chenxi ZHANG, Yiqi HU, Zeshui XU, Hao LIUThe authors regret the error.